Platelet-rich Plasma versus Corticosteroid Injection for the Treatment of Lateral Epicondylitis – A Prospective Randomised Controlled Study - Suryakanth Kalluraya; Anand Varma; Gujjala Venkata Naga Yeswanth (Indian Journal of Physical Medicine & Rehabilitation)
Introduction: Lateral epicondylitis, commonly known as tennis elbow, is one of the most common chronic disabling painful conditions that affect the forearm’s common extensor tendons. This study aimed to compare the effectiveness of platelet-rich plasma (PRP) versus corticosteroid injection in the treatment of lateral epicondylitis. Aims: The purpose of this study is to compare the efficacy of PRP versus corticosteroid injection in the treatment of lateral epicondylitis, focusing on the early response. Settings and Design: This was a prospective randomised controlled study. Materials and Methods: This study was a prospective randomised control trial of 100 patients, clinically diagnosed with lateral epicondylitis in Karnataka Institute of Medical Sciences Hospital, Hubli. Patients were randomly allocated (1:1) using computer-generated random numbers to two groups. Group A received corticosteroid injection. Group B received PRP injection. Outcome assessment was done using the Oxford Elbow Score (OES), Visual Analogue Scale (VAS), Patient-rated Tennis Elbow Evaluation (PRTEE) and Disabilities of Arm, Shoulder and Hand Score (DASH). All patients were followed up at regular intervals of 2 weeks, 4 weeks, 3 months and 6 months post-injection. Statistical Analysis Used: Using SPSS Statistics version 25 software, statistical analysis was done. Results: Pre–injection, the mean OES, VAS, PRTEE and DASH scores were similar in both the groups with insignificant P value. The mean pre-injection OES, VAS, PRTEE and DASH scores in the corticosteroid group were 11.22, 7.88, 75.950 and 69.364, whereas in the PRP group, it was 10.66, 7.96, 76.170 and 69.466, with P = 0.165, 0.322, 0.834 and 0.869, respectively. At the end of 6 months in the corticosteroid group, the mean score of OES increased from 11.22 ± 1.71 to 38.94 ± 5.17, VAS decreased from 7.88 ± 0.385 to 1.74 ± 1.24, PRTEE decreased from 75.95 ± 4.86 to 24.3 ± 12 and DASH decreased from 69.36 ± 2.90 to 23.31 ± 11.5, with a significant P < 0.005. At the end of 6 months in the PRP group, the mean scores of OES increased from 10.66 ± 2.07 to 45.38 ± 1.41, VAS decreased from 7.96 ± 0.45 to 0.06 ± 0.31, PRTEE decreased from 76.1 ± 5.04 to 7.47 ± 3.16 and DASH decreased from 69.47 ± 3.44 to 7.78 ± 2.65, with a significant P < 0.005. Conclusion: We concluded that patients treated with PRP had significantly reduced pain, increased functional activity, less recurrence and without requirement of any further intervention, outperforming corticosteroid injection effect at the end of 6 months follow up.